A revised model for Darcy-Forchheimer flow of Maxwell nanofluid subject to convective boundary condition - Muhammad, Taseer; Alsaedi, Ahmed; Shehzad, Sabir Ali; Hayat, Tasawar (Chinese journal of physics (Taipei), 2017)
•Darcy–Forchheimer flow of Maxwell nanofluid is modeled.•Flow is induced by a linear stretching surface.•Uniform magnetic field and convective surface are accounted.•Nanofluid model includes the effects of Brownian motion and thermophoresis.•Newly proposed condition associated with mass flux is incorporated. This research article provides the magnetohydrodynamic (MHD) boundary-layer flow of Maxwell nanomaterial saturating a non-Darcy porous medium. Flow is generated due to a stretching surface. The flow in porous media is characterized by considering the Darcy–Forchheimer based model. Novel features of Brownian motion and thermophoresis are retained. A uniform applied magnetic field is employed. Small magnetic Reynolds number and boundary-layer assumptions are employed in the formulation. Simultaneous effects of convective heat and zero nanoparticles mass flux conditions are imposed. Transformation procedure is adopted to convert the partial differential system into the nonlinear ordinary differential system. The governing nonlinear ordinary differential system is solved for the convergent homotopic solutions. Convergence analysis is performed through the plot and numerical data. Graphs have been plotted in order to analyze the temperature and concentration profiles by distinct pertinent flow parameters. Local Nusselt number is also computed and examined.